2016
DOI: 10.1039/c6cp00583g
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics of anhydrous glycolipid self-assembly in lamellar and hexagonal phases

Abstract: The molecular dynamics of a synthetic branched chain glycolipid, 2-decyl-tetradecyl-β-d-maltoside (C14-10G2), in the dry assemblage of smectic and columnar liquid crystal phases has been studied by dielectric spectroscopy as a function of frequency and temperature during the cooling process. Strong relaxation modes were observed corresponding to the tilted smectic and columnar phases, respectively. At low frequency (∼900 Hz to 1 kHz) in the smectic phase, Process I* was observed due to the tilted sugar bilayer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Dielectric relaxation spectroscopy (DRS), owing to its sensibility to all kinds of polarization, has been extensively applied to study the dynamics and structure of mixed solutions, including their phase transition and the number of binding solvents of aggregations. For a surfactant solution that forms aggregates, i.e., a heterogeneous system, the phase volume fraction, dielectric parameters, and the number of free and bound solvents of each component phase in the heterogeneous system can be obtained by establishing an appropriate model. In this way, the microstructure of the system can be described better.…”
Section: Introductionmentioning
confidence: 99%
“…Dielectric relaxation spectroscopy (DRS), owing to its sensibility to all kinds of polarization, has been extensively applied to study the dynamics and structure of mixed solutions, including their phase transition and the number of binding solvents of aggregations. For a surfactant solution that forms aggregates, i.e., a heterogeneous system, the phase volume fraction, dielectric parameters, and the number of free and bound solvents of each component phase in the heterogeneous system can be obtained by establishing an appropriate model. In this way, the microstructure of the system can be described better.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have observed that substitution of the 14 with 16 glycosidic linkage within the headgroup significantly decreases bilayer spacing and modifies the pattern of inter-headgroup hydrogen-bonding [17]. Introducing branched lipid chains, on the other hand, alters the interactions of the lamellar assembly, resulting into more fluid-like hydrophobic regions [17], and thus promotes polymorphism from columnar to smectic phases in Guerbet maltosides [29]. Recently, an improved and optimised simulation technique based on replica exchange molecular dynamics (REMD) has been developed and may be used for such challenging and computationally intensive problems [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Since the number of the HBs is smaller for glucosides than that of the maltosides the relaxation for 31,32 . Typically, maltosides have an order of magnitude lower relaxation frequency than that of the glucosides.…”
Section: Dielectric Behavior Of Glycosidesmentioning
confidence: 99%
“…Therefore, in this review the lyotropic nomenclature is preferred for the dry thermotropic GL assemblies. Recent studies of dry GL thermotropic phases lamellar, hexagonal and bicontinuous cubic include molecular dynamics using dielectric spectroscopy 31,32 , which established the tilted organization of bilayer 33,34 and possible exploitation of the ferroelectric property 35 . Some fundamental ideas have emerged from thermotropic studies of GLs such as the fact that the cubic phases may be induced by mixing the hexagonal and lamellar phases 36 .…”
Section: Introductionmentioning
confidence: 99%